The Usage of Web 2.0 as a Media Promotion in Indonesia University Libraries - Anna, Nove E. Variant (Record and Library Journal, 2015)
The usage of web 2.0 has become popular among young people in Indonesia. One of the purpose of using web 2.0 is for promotion in some university libraries. The emerging of the web 2.0 as promotional media is corelating with the development of digital library. The paper aims are (1) to describe the usage of web 2.0 for academic libraries promotion. (2) to describe the information / content of those web 2.0. (3) to describe the promotion activity through web 2.0. This research population is all university libraries in Indonesia, but only 40 university libraries that conduct promotion through web 2.0. The website observation is done between May-July 2013. The research results are (1) the university libraries in Indonesia are use facebook, twitter, and flicker to promote library programs and interaction with users. The web 2.0 consist of information about new book release, user education, general information about library services, and information literacy. (3) some of univerity libraries taking seriously and actively promote their library services, but some of them are donât use the web 2.0.